Pengaruh Komite Madrasah dalam Meningkatkan Mutu Pendidikan Islam dan Kinerja Guru di Madrasah Aliyah Negeri 3 Tangerang - Syarif Budiman; Encep Syarifudin; Rijal Firdaos (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study aims to analyze the influence of the madrasah committee in improving the quality of Islamic education and teacher performance at Madrasah Aliyah Negeri 3 Tangerang. The madrasah committee has a strategic role in supporting education management, including improving the quality of learning, supervising teacher performance, and strengthening Islamic values in the school environment. The research method used is a quantitative approach with data collection techniques through questionnaires, interviews, and observations. The results of the study show that the active role of the madrasah committee contributes significantly to the improvement of the quality of Islamic education and teacher performance. The madrasah committee plays a role in providing input to the school, improving the welfare of teachers, and creating a conducive learning environment. Thus, the synergy between the madrasah committee and the school is a key factor in creating quality Islamic education.